2012
DOI: 10.1258/shorts.2011.011126
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for elective colorectal surgery using a video: a questionnaire-based observational study

Abstract: ObjectiveEvery patient has a perception about surgery and psychological preparation of the patient has an important impact on their postoperative recovery and outcome. In this study we looked at impact of a visual educational aid, in the form of a patient DVD on outcome following colorectal surgery within an enhanced recovery programme (ERP).DesignWe carried out a prospective analysis of a consecutive series of patients undergoing elective colorectal resection. All patients were given information about their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…On introduction of the video, we carried out an observational study where questionnaires were given to patients to study understanding and confidence levels on discharge from hospital on the use of a video for psychological preparation following colorectal surgery. We concluded that supplementing video education with both oral and printed information was better in preparing patients psychologically for surgery and helping improve short‐term outcomes in an enhanced recovery programme . However, this observational study was limited as surveying one's patients can lead to an overstated positive feedback.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On introduction of the video, we carried out an observational study where questionnaires were given to patients to study understanding and confidence levels on discharge from hospital on the use of a video for psychological preparation following colorectal surgery. We concluded that supplementing video education with both oral and printed information was better in preparing patients psychologically for surgery and helping improve short‐term outcomes in an enhanced recovery programme . However, this observational study was limited as surveying one's patients can lead to an overstated positive feedback.…”
Section: Discussionmentioning
confidence: 93%
“…Audiovisual presentation in the form of a video may be a useful tool in the psychological preparation of patients for surgery. We recently published results of a questionnaire‐based observational study on the use of video education, which showed it to be a better source of information than printed material . We concluded that supplementing video education with both oral and printed information is better in preparing patients psychologically for surgery and to help improve short‐term outcomes in an enhanced recovery programme.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Patients scheduled for elective colorectal surgery were shown videos about preoperative evaluation and postoperative recovery; they felt emotionally stable and motivated after watching the videos. [ 11 ] In pediatric outpatient surgery, when parents were educated about anesthesia using videos, the APAIS score significantly improved, and the level of knowledge about anesthesia also increased. [ 12 ] A video on preanesthetic education shown to Spanish patients in their native language significantly reduced anxiety compared to those who did not watch it.…”
Section: Discussionmentioning
confidence: 99%
“…A seleção ou triagem de doadores é a maneira que se tem de buscar uma maior segurança transfusional e evitar uma transmissão de agente infeccioso dentro do período de janela imunológica, excluindo-se aqueles com fatores de risco para os agentes transmissíveis por transfusão e aqueles com sinais ou sintomas que possam denotar uma infecção. O vídeo tem sido utilizado como ferramenta de educação de pacientes, profissionais da saúde e de cuidadores, em situações tão variadas quanto a obtenção de consentimentos esclarecidos para cirurgias ou procedimentos médicos; para diminuir a ansiedade pré procedimentos cirúrgicos, invasivos ou clínicos; aumentar a aderência a tratamentos crônicos, como por exemplo a terapia antirretroviral em pacientes com SIDA; aumentar a satisfação com o atendimento; orientar o uso adequado de dispositivos e medicamentos, como no tratamento da asma e para modificar ou induzir comportamentos, como na captação de doadores de sangue e visando à mudança de estilo de vida em portadores de diabetes mellitus (SAMPAIO-SÁ, 2008;DYSON, 2010;CORBETT, 2000;LUCK, 1999;FRANCE, 2011;TORABI, 2000;KINNANE, 2008;THOMAS, 2000;IHEDIOHA, 2013;MORLEY, 2013;THOMAS, 1999;ARMSTRONG, 2010;LORENZO-RIVERO, 2012;IHEDIOHA, 2012;SCHOFIELD, 2008;SARASON, 1992;HAHN, 2005;HARRISON, 2001;CAREY, 2007).…”
Section: A Informação Como Ferramenta Para Aumentar a Segurança Transunclassified